1986
DOI: 10.1203/00006450-198603000-00004
|View full text |Cite
|
Sign up to set email alerts
|

Controlled Hypercapnia and Neonatal Cerebral Artery Doppler Ultrasound Waveforms

Abstract: ABSTRACT. Eleven normal term infants undergoing res-The study of cerebral hemodynamics in the newborn infant by Doppler ultrasound is attractive because it is convenient, noninvasive, and apparently safe. There are a number of reports describing this technique in many different pathological situations (1-10) but few which describe findings in normal babies (1 1, 12). There is little information on the hemodynamic processes that underlie changes in Doppler ultrasound readings from the cerebral vessels of newbor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
12
1

Year Published

1987
1987
2014
2014

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(15 citation statements)
references
References 20 publications
2
12
1
Order By: Relevance
“…In this study, we have shown that term infants with apnea or ALTE demonstrate cerebral vasodilation and increased cerebrovascular flow in response to elevated CO 2 . This is consistent with previous studies indicating that well-term newborns exhibit an increased CBF in response to elevated CO 2 [21,22]. Thus, the presence of apnea -which can be associated with impaired respiratory drive and immature autonomic innervationis not associated with impaired cerebral vascular responses to CO 2 in full-term infants.…”
Section: Resultssupporting
confidence: 81%
“…In this study, we have shown that term infants with apnea or ALTE demonstrate cerebral vasodilation and increased cerebrovascular flow in response to elevated CO 2 . This is consistent with previous studies indicating that well-term newborns exhibit an increased CBF in response to elevated CO 2 [21,22]. Thus, the presence of apnea -which can be associated with impaired respiratory drive and immature autonomic innervationis not associated with impaired cerebral vascular responses to CO 2 in full-term infants.…”
Section: Resultssupporting
confidence: 81%
“…nonpulsatile) component of flow than there is in the systolic (i.e. pulsatile) component of blood flow (19). Inasmuch as changes induced in cerebral blood flow by other mechanisms such as blood pressure changes, may have different effects on the relative changes in pulsatile and nonpulsatile components of blood flow, our results may not be reproduced if changes in cerebral blood flow were induced by other stimuli.…”
Section: Discussioncontrasting
confidence: 52%
“…Thus, when downstream properties (representing vascular impedance) are incorporated into mathematical or physical models, blood flow can become dependent on resistance. 4,5 Although this has been corroborated during postischemic hyperemia in the brachial artery 6 and hypercapnea in neonatal cerebral arteries, 7 the dependence of RI on vascular resistance varies considerably among vascular beds. In rabbit kidneys perfused ex vivo with increasing concentrations of phenylephrine, 8 there was only a slight increase in RI despite a broad range of resistance not observed in vivo ( Figure 1) and the inability of vasoconstrictors or vasodilators to appropriately alter RI has also been observed in the uterine, 9 carotid, 10 and retinal 11 circulations.…”
mentioning
confidence: 99%